The determinants of muslim purchase intention towards the non-muslim halal packaged food manufacturer in Klang Valley / Mohd Hafizuddin Abu Bakar - Abu Bakar, Mohd Hafizuddin (Faculty of Business and Manegement, 2018)
The research questions how can halal awareness, Islamic brand and product ingredients have a significant relationship on Muslim 's intention to purchase a Non-Muslim's halal packaged food. Next, for research objectives are to investigate there is a significant relationship of between halal awareness, Islamic-brand and product ingredients towards the Muslim's intention to purchase a Non-Muslim's halal packaged food. 150 questionnaires will be distributed to Muslim consumers in Malaysia. Variables of halal awareness, Islamic brand and product ingredient are recognized as an independent variables and Muslim's purchase intention as a dependent variable. Descriptive analysis, reliability analysis and correlation analysis will be conducted using SPSS Statistic 22. The result is collect which is for halal awareness Ho is able to accept because p-value for this variable is 0.769 which is higher than significant level 0.05. There is no significant relationship between halal awareness and Muslims intention to purchase a Non-Muslims halal packaged food. Next, for Islamic brand Ho able to reject because p-value for this variable is 0.003 which is less than significant level 0.05. There is a significant relationship between Islamic brand and Muslims intention to purchase a Non-Muslims halal packaged food. Hence, it shows that Islamic Brand is positively related with intention to purchase a Non-Muslims halal packaged food. Lastly, for product ingredients Ho able to reject because p-value for this variable is 0.043 which is less than significant level 0.05. There is a significant relationship between product ingredients and Muslims intention to purchase a Non-Muslims halal packaged food. Hence, it shows that Islamic Brand is positively related with intention to purchase a Non-Muslims halal packaged food.